A2 incompatible kidney transplantation does not adversely affect graft or patient survival. Issue 5 (17th March 2016) - Forbes, Rachel C.; Feurer, Irene D.; Shaffer, David
Abstract: Background: The new United Network for Organ Sharing (UNOS) kidney allocation system (KAS) incorporates A2 and A2B to B transplantation to reduce wait times for blood group B candidates. Few studies have employed multicenter data or comprehensively defined donor‐to‐recipient ABO classification systems. Methods: We retrospectively analyzed UNOS data from 1987–2013 to evaluate the effect of A2 incompatible (A2i) kidney transplantation on graft and patient survival. Records of 314 056 adults (340 150 transplants) were classified as A2i (560 transplants in A2 to B or O, A2B to B) or compatible. Methods included Kaplan– Meier survival and multivariable Cox proportional hazards regression. Results: Graft survival after A2i transplant (median = 116 months) did not differ (log‐rank p ≥ 0.101) from any compatible class (medians = 106–119 months); there was no effect of A2i on patient survival (log‐rank p ≥ 0.286). After adjusting for age, race, donor type, pancreas, or previous kidney transplant, A2i was not associated with graft (p ≥ 0.263) or patient (p ≥ 0.060) survival in this largest cohort to date. Conclusions: A2i kidney transplantation does not adversely affect graft or patient survival. A2i kidney transplantation has been included in the new KAS and represents a viable option for transplant centers to increase transplant volume and reduce wait times for disadvantaged B waitlist recipients.